Photocatalytic, self-cleaning, antireflective coating for photovoltaic panels: Characterization and monitoring in real conditions. (1st January 2018) - Arabatzis, Ioannis; Todorova, Nadia; Fasaki, Ioanna; Tsesmeli, Chrysovalanti; Peppas, Antonis; Li, Wen Xin; Zhao, Zhiwei
Graphical abstract: Highlights: Antireflective, self-cleaning and antistatic coating for photovoltaics. Thermally and UV resistant glass coating stable after sand blasting. One step application and average 5–6% power gain for long term operation. Excellent 20–30% power gain under diffused light and high incident angle. Abstract: A major problem in the operation of photovoltaic (PV) panels is the need for frequent maintenance and cleaning. In the present work, the effect of a self-cleaning, photocatalytic, antireflective glass coating on the efficiency of PV panels is investigated. The optical and photocatalytic properties of the coating were determined via UV–vis spectroscopy and degradation of organic pollutant Methylene Blue, respectively. Increased light transmittance in the visible light region and enhanced self-cleaning of the coated in comparison to the uncoated glass was demonstrated. The adhesion and the stability of the coating were tested in conditions of thermal fluctuations, UV weathering and sandblasting. The outdoor performance of coated and uncoated PV panels and arrays were monitored for several months at different climate conditions (Greece and China) in order the extra energy produced due to coating to be measured. An average 5–6% gain was found for both cases for the entire period of time. It was established that specific conditions such as intensity and angle of the incident light, occurrence of rain and sand storms influence significantly the power difference ( ΔPm ) between coated and uncoated PV panels. The increase of ΔPm under diffused light (cloudy day) and irradiation with high incident angle (morning, evening) reached ∼20% and 30% respectively, that were related to the anti-reflecting property of the glass coating. The coated surface showed better dust removal ability due to its superhydrophilicity (θ = 6°). The superior efficiency of coated panels as well as the low-cost spraying procedure without any post-deposition treatment render the nanocomposite SurfaShield G coating very important especially for northern regions with limited sunlight periods.